Sealing by soldering of microblock packages made of diamagnetic alloys using high-frequency heating - Lanin, V. L.; Grishchenko, Yu. N. (Technology and design in electronic equipment, 2018)
The main difficulties of application of high-frequency (HF) heating for sealing by soldering of microblock packages made of aluminum alloys is the low efficiency of heating, long processing time and considerable heating of the internal electronic module while sealing.The purpose of this study was to use effectively the physical phenomena of HF heating in order to optimize the HF heating parameters of sealing by soldering using fusible solders of microwave microblock packages made of diamagnetic alloys.Effects of HF heating (superficial, proximity and concentration of power lines) of the electromagnetic field are applied to sealing using soldering of microwave microblock packages made of diamagnetic alloys. The optimized parameters of HF heating provide energy efficiency and productivity of sealing: frequency of the electromagnetic field and the inductor design.When soldering microelectronic devices containing electronic parts sensitive to the electric field component, the energy of electromagnetic field in the package should be significantly lower than the energy of elements degradation, in which case the skin layer reaches the field penetration depth which is equal to 4 package thickness values. In order to increase the HF heating efficiency, there should be a concentration of the inductor current on the package surface facing the inductor, which is done by using a ferrite magnetic core. Using a ferrite magnetic core inside the inductor concentrates tension of magnetic field due to concentration of power lines of magnetic field in 1,2–1,3 times.The optimal frequency range for HF soldering is 0,4–2,0 MHz when at electromagnetic field penetration depth into the material of the package equal to 4 thickness values of the skin layer, the field strength is 152 times weaker in comparison with the surface.